Encapsulation of Cinnamaldehyde from Cinnamon Essential Oils in Cyclodextrin - C Chimvaree; R Tepsorn; S Supapvanich; C Wongs-Aree; V Srilaong; P Boonyaritthongchai (My University, 2020)
Abstract Cinnamaldehyde is the major compound in cinnamon essential oil which has effective inhibiting the microbial growth and revealed low physicochemical stability, low solubility in water. The aim of this study was the encapsulation of cinnamaldehyde in β-cyclodextrin in order to obtain a complex which can be used for preserving fresh-cut produce. The encapsulated complex cinnamaldehyde/ β-cyclodextrin was prepared using the inclusion complex method. The various ratios of cinnamaldehyde/β-cyclodextrin on cinnamaldehyde releasing efficiency was investigated. The various ratios of cinnamaldehyde/β-cyclodextrin as 50:50, 40:60, 30:70 and 25:75 were monitored. Encapsulation efficiency (%EE) and encapsulation capacity (%EC) of encapsulated cinnamaldehyde powder were analyzed. The results showed that the ratio at 25:70 cinnamaldehyde/β-cyclodextrin showed the highest %EC and %EE when compared with other treatments. The ratio at 25:75 had faster control release in first 3 h. Antimicrobial activity was tested against two strains of gram-positive ( Staphylococcus aureus and Bacillus cereus ) and two strains of gram-negative ( Escherichia coli and Pseudomonas aeruginosa ) bacteria. β-cyclodextrin with encapsulated cinnamaldehyde exhibited good inhibitory effect against all tested bacterial strains.
Keywords: Drug Solubulity and Delivery Systems